The Impact of Port Congestion on The Nigerian Economy (International Journal of Scientific Research and Management (IJSRM), 2015)
This research assessed the impact of port congestion on the Nigerian economy. It also examined critically, the factors affecting port performance and its impact on the Nigerian economy. Relevant literatures on port congestion and its effects on port productivity were reviewed. Secondary data were obtained from Central Bank Statistical Bulletin and Nigerian Ports Authority annual bulletin. Data for GDP, Imports, Exports and ports indicator of utilization and of service (Ship calls, Cargo throughput) for a period of 18 years (1995 - 2012) were analyzed using Multiple Regression with the aid of Statistical Package for Social Sciences (SPSS V.20.0), to determine the degree of significance of variables affecting port economic drivers. From the result of the analysis, it was deduced that imports, exports, cargo throughput and berth occupancy ratio correlate significantly and are statistically impacted by GDP variable. Nigerian economy is dependent on the export of Crude oil and Agricultural produce to earn foreign income, while our industries is dependent to a large extent, on the importation of materials needed for their consumption or production activities. Therefore, stagnation in port operations (ports congestion) will have dire economic consequences on the economic growth of the nation. Expanding gate operating hours will maximise the use of off-peak roadway capacity. Nigerian ports should start offering 24 hour/day gate operations to improve berth utilisation rate, reduced cargo dwell time, enhanced ship turnaround time. This will discourage the diversion of Nigeria bound cargo to ports of neighbouring countries, which implies improved revenue yield to the Nigerian economy. From the test of hypothesis, using the statistical student t-test, there is a strong, statistical, significant relationship between Gross Domestic Product and port performance economic drivers (imports, exports, ship calls and cargo throughput).